2023
DOI: 10.23887/jet.v7i2.52194
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers’ Use and Usefulness of Blackboard Learning Management Systems for Self-Regulated Learning

Abstract: Although BLB has many applications students use, it is not clear which applications are used most and perceived most useful for Self-Regulated Learning (SRL). The objective of this research is to establish applications pre-service teachers use most and perceive as most useful for SRL. The study used a cross-sectional survey design with 120 technology education undergraduate pre-service teachers. A questionnaire was distributed during the Technology Education period and collected after 45 minutes. Principal Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Likewise, Ref. [56] also used an online learning tool called Blackboard to study SRL among African students. The authors found that, like some applications used by the students, Blackboard was also helpful for their SRL.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…Likewise, Ref. [56] also used an online learning tool called Blackboard to study SRL among African students. The authors found that, like some applications used by the students, Blackboard was also helpful for their SRL.…”
Section: Self-regulated Learningmentioning
confidence: 99%